Characterization of electroless nickel doped electrolytic manganese dioxide - Madzlan Aziz; Jamil Yusof; Raizul Azita Abd. Rashid; Suhaila Mohd. Sanip; Regional Conference on Solid State Science and Technology (20th : 2003 : Lumut, Perak) (Skudai : Universiti Teknologi Malaysia, 2003)
51